Starch-rich plant foods 780,000 y ago: Evidence from Acheulian percussive stone tools - Hadar Ahituv; Amanda G. Henry; Yoel Melamed; Naama Goren-Inbar; Corrie Bakels; Lyudmila Shumilovskikh; Dan Cabanes; Jeffery R. Stone; Walter F. Rowe; Nira Alperson-Afil (Proceedings of the National Academy of Sciences, 2025)
In contrast to animal foods, wild plants often require long, multistep processing techniques that involve significant cognitive skills and advanced toolkits to perform. These costs are thought to have hindered how hominins used these foods and delayed their adoption into our diets. Through the analysis of starch grains preserved on basalt anvils and percussors, we demonstrate that a wide variety of plants were processed by Middle Pleistocene hominins at the site of Gesher Benot Ya’aqov in Israel (33° 00’ 30” N, 35° 37’ 30” E), at least 780,000 y ago. These results further indicate the advanced cognitive abilities of our early ancestors, including their ability to collect plants from varying distances and from a wide range of habitats and to mechanically process them using percussive tools.